IMPLEMENTATION OF LEARNING THE KITAB KUNING THROUGH ACTIVE METHODS IN THE PERSPECTIVE OF HADITH AT MMA SUNAN DRAJAT LAMONGAN - Moh. Faizal Hidayatullah; Muhid; Muhammad Tareh Aziz (Journal of Practice Learning and Educational Development, 2025)
This study analyzes the implementation of active learning methods in the teaching of kitab kuning at MMA Sunan Drajat Lamongan through a hadith-based educational approach. Kitab kuning, as classical Islamic texts written in unvowelized Arabic script, often poses challenges for students, especially those lacking foundational knowledge in Arabic grammar such as nahwu and sharaf. Traditional passive teaching methods are often ineffective in fostering deep comprehension and student engagement. To address these issues, this study explores the use of active learning strategies such as discussion (musyawaroh), interactive dialogue, group work, and role-playing. A qualitative research approach was employed, using observation, interviews, and documentation for data collection. The findings indicate that active learning methods create a more interactive learning environment, enhance textual understanding, and help develop students’ confidence, critical thinking, and analytical skills. Moreover, these methods are strongly rooted in the educational practices of Prophet Muhammad (SAW), who frequently applied participatory, contextual, and communicative approaches in his teaching. Thus, active learning from a hadith perspective not only serves as a pedagogical innovation but also revives prophetic educational values that remain relevant and effective in the context of modern Islamic education.